Long-range transport of Xe-133 emissions under convective and non-convective conditions. (September 2017) - Kuśmierczyk-Michulec, J.; Krysta, M.; Kalinowski, M.; Hoffmann, E.; Baré, J.
Abstract: To investigate the transport of xenon emissions, the Provisional Technical Secretariat (PTS) operates an Atmospheric Transport Modelling (ATM) system based on the Lagrangian Particle Dispersion Model FLEXPART. The air mass trajectory ideally provides a "link" between a radionuclide release and a detection confirmed by radionuclide measurements. This paper investigates the long-range transport of Xe-133 emissions under convective and non-convective conditions, with special emphasis on evaluating the changes in the simulated activity concentration values due to the inclusion of the convective transport in the ATM simulations. For that purpose a series of 14 day forward simulations, with and without convective transport, released daily in the period from 1 January 2011 to 30 June 2013, were analysed. The release point was at the ANSTO facility in Australia. The simulated activity concentrations for the period January 2011 to February 2012 were calculated using the daily emission values provided by the ANSTO facility; outside the aforementioned period, the median daily emission value was used. In the simulations the analysed meteorological input data provided by the European Centre for Medium-Range Weather Forecasts (ECMWF) were used with the spatial resolution of 0.5°. It was found that the long-range transport of Xe-133 emissions under convective conditions, where convection was included in the ATM simulation, led to a small decrease in the activity concentration, as compared to transport without convection. In special cases related to deep convection, the opposite effect was observed. Availability of both daily emission values and measured Xe-133 activity concentration values was an opportunity to validate the simulations. Based on the paired t -test, a 95% confidence interval for the true mean difference between simulations without convective transport and measurements was constructed. It was estimated that the overall uncertainty lies between 0.08 and 0.25 mBq/m 3 . The uncertainty for the simulations with the convective transport included is slighted shifted to the lower values and is in the range between 0.06 and 0.20 mBq/m 3 . Highlights: For the first time ATM simulations use one full year of daily Xe-133 emission data. ATM simulations are validated using measured Xe-133 activity concentrations. Inclusion of the convective transport in ATM simulations leads to minor changes. Deep convection decreases the number of potential detections. Seasonal changes in the number of potential detections are demonstrated.